Drainage Capacity Analysis in The Area of Angke Jaya Tambora West Jakarta - Bagas, Naufal Alfathan (NAROTAMA UNIVERSITY, Indonesia, 2020)
Drainage is used to reduce and remove excess water in an area so that the area can be optimally enabled. This research aims to analyze and examine the drainage problems in the Angke Jaya Tambora West Jakarta Housing area, the drain channels are poorly maintained and often flooding. The data used in this study are primary and secondary, in the planning of flood debt calculations used 2nd anniversary. For the calculation of flood discharge plan to use rational method and coupled with the discharge of flood household, and the result will be compared with existing conditions of drainage channels in the residential area Angke Jaya Tambora West Jakarta. Obtained flood discharge plan of 13.225 m3/sec, for the existing condition of drainage channels 5 channels enter the category is not safe because the condition of existing capacity of channels is less than flood discharge plan, namely channels A4, D5, D6, D8, and D9. The planning of the wells to accommodate the excess discharge flooding, and it takes 19 pieces of replacement wells on the A4 channel, 1 on the D5, D, D8, and D9 channels.